Osteocyte physiology and response to fluid shear stress are impaired following exposure to cobalt and chromium: Implications for bone health following joint replacement. Issue 8 (14th October 2016) - Shah, Karan M.; Orton, Peter; Mani, Nick; Wilkinson, Jeremy Mark; Gartland, Alison
ABSTRACT: The effects of metal ion exposure on osteocytes, the most abundant cell type in bone and responsible for coordinating bone remodeling, remain unclear. However, several studies have previously shown that exposure to cobalt (Co 2+ ) and chromium (Cr 3+ ), at concentrations equivalent to those found clinically, affect osteoblast and osteoclast survival and function. In this study, we tested the hypothesis that metal ions would similarly impair the normal physiology of osteocytes. The survival, dendritic morphology, and response to fluid shear stress of the mature osteocyte‐like cell‐line MLO‐Y4 following exposure to clinically relevant concentrations and combinations of Co and Cr ions were measured in 2D‐culture. Exposure of MLO‐Y4 cells to metal ions reduced cell number, increased dendrites per cell and increased dendrite length. We found that combinations of metal ions had a greater effect than the individual ions alone, and that Co 2+ had a predominate effect on changes to cell numbers and dendrites. Combined metal ion exposure blunted the responses of the MLO‐Y4 cells to fluid shear stress, including reducing the intracellular calcium responses and modulation of genes for the osteocyte markers Cx43 and Gp38, and the signaling molecules RANKL and Dkk‐1 . Finally, we demonstrated that in the late osteoblasts/early osteocytes cell line MLO‐A5 that Co 2+ exposure had no effect on mineralization, but Cr 3+ treatment inhibited mineralization in a dose‐dependent manner, without affecting cell viability. Taken together, these data indicate that metal exposure can directly affect osteocyte physiology, with potential implications for bone health including osseointegration of cementless components, and periprosthetic bone remodeling. © 2016 The Authors. Journal of Orthopaedic Research Published by Wiley Periodicals, Inc. on behalf of Orthopaedic Research Society. J Orthop Res 35:1716–1723, 2017.